2011
DOI: 10.1002/ana.22331
|View full text |Cite
|
Sign up to set email alerts
|

Infantile muscular dystrophy in Canadian aboriginals is an αB‐crystallinopathy

Abstract: Objective-A recessively transmitted fatal hypertonic infantile muscular dystrophy has been described in Canadian Aboriginals. The affected infants present with progressive limb and axial muscle stiffness, develop severe respiratory insufficiency, and most die in the first year of life. We sought to determine the genetic basis of this disease.Methods-We performed histochemical, immunocytochemical, electron microscopy and molecular genetic studies in a cohort of 12 patients affected by this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 23 publications
4
41
0
1
Order By: Relevance
“…Similarly, several other naturally-occurring mutations in the C-terminal region of Hsp27; P182L [229], P182S [237], R140G [238] and K141Q [239] cause distal HMN. Other rarer forms of fibrillar neuropathy have been identified, with deletions in the gene encoding Bc (CRYAB) resulting in the absence of the protein from affected muscle fibres [240]. A naturally-occurring deletion of a single nucleotide base in the CRYAB gene has been described and leads to a frameshift mutation in the C-terminal region of the resulting Bc protein [216].…”
Section: Mutations In the C-terminal Regionmentioning
confidence: 99%
“…Similarly, several other naturally-occurring mutations in the C-terminal region of Hsp27; P182L [229], P182S [237], R140G [238] and K141Q [239] cause distal HMN. Other rarer forms of fibrillar neuropathy have been identified, with deletions in the gene encoding Bc (CRYAB) resulting in the absence of the protein from affected muscle fibres [240]. A naturally-occurring deletion of a single nucleotide base in the CRYAB gene has been described and leads to a frameshift mutation in the C-terminal region of the resulting Bc protein [216].…”
Section: Mutations In the C-terminal Regionmentioning
confidence: 99%
“…For example, myotilinopathy was reported as limb girdle muscular dystrophy 1A by the clinical criteria, 36,37 and the ␣B-crystallinopathy of Canadian aboriginals was reported under the rubric of a fatal infantile muscular dystrophy. 38,39 Finally, the clinical and pathologic features of the FHL1 muscular dystrophies can be typical of MFMs, but MFM pathology has not been described or may have been overlooked in some cases of FHL1-related muscular dystrophies. The presence of reducing bodies points to a mutation in the LIM2 domain of FHL1.…”
Section: Org)mentioning
confidence: 99%
“…This may be similar to muscles of patients with the R120G mutation who have loss of myosin in their muscle cells (Vicart et al 1998 ;Fardeau et al 1978 ). Potentially, oxidative, slow-twitch fi bers, which have the highest levels of αB-crystallin and are enriched in large truncal muscles, are preferentially degraded in the DKO mice (Brady et al 2001 ) and in patients with recessive CRYAB mutations (Forrest et al 2011 ;Del Bigio et al 2011 ). Neppl and colleagues showed that 1 year old DKO mice have a signifi cantly reduced number of satellite cells in their skeletal muscle and a reduced ability to regenerate muscle following cardiotoxin-induced injury, shown by decreased cross-sectional myofi ber area and increased fi brosis 2 weeks post-injury, indicating a potential role for αB-crystallin in skeletal muscle regeneration (Neppl et al 2014 ).…”
Section: Recessive Mutationsmentioning
confidence: 98%